Mindful Learning-Based Cognitive Load Management Model in Elementary School Mathematics Learning - I Made Tegeh; I Made Suarjana; Gede Weda Rukmana (Universitas Pendidikan Ganesha, 2025)
Many elementary school students still experience difficulties in understanding mathematical concepts due to the high cognitive load during the learning process. This leads to low levels of concentration and learning motivation. The purpose of this study is to develop a Cognitive Load Management (CLM) model based on Mindful Learning to reduce students' cognitive load and improve the effectiveness of mathematics learning. This study is a type of Research and Development (R&D) using the ADDIE model. The research subjects consisted of 2 instructional experts and 2 subject matter experts. The trial subjects included 1 teacher/practitioner, 3 students (individual trials), and 6 students (small group trials). Data collection methods included observation, interviews, questionnaires, and tests. The instruments used were questionnaires and test items. The data analysis techniques used were qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistics. Validation results by instructional experts showed a score of 94% (very valid), and material expert validation reached 95% (very valid). The teacher's assessment of the model implementation was 96% (very practical), individual trials scored 93.5% (very practical), and small group trials scored 90% (very practical). The effectiveness test results showed a significant difference in students' learning outcomes before and after the implementation of the Cognitive Load Management model based on Mindful Learning in mathematics learning. It can be concluded that the CLM model based on Mindful Learning is feasible to be used in mathematics instruction as it is effective in helping students manage cognitive load while enhancing focus and conceptual understanding.